A study of the PfNT3 in Plasmodium falciparum - Sahu Pratima Kumari,; Panda Maheswar,; Patra Satyajit,; Das Sidhartha,; Satyamoorthy K,; Mohanty Dipika, (Penerbit UKM, 2015)
Previous genetic studies demonstrated that survival and proliferation of Plasmodium falciparum parasites is dependent on salvage of essential purines from the host. Plasmodium falciparum, the causative agent of the most lethal form of human malaria lacks the enzymes required for de novo synthesis of purines. Analysis of the hypothetical nucleoside/nucleobase transporter protein, the gene product of PfNT3 (PF14_0662) gene in P. falciparum parasites was carried out by localisation, in view of a novel chemotherapeutic target. Immunoblotting, immunofluorescent and immunoelectron microscopic localization of PfNT3 was demonstrated using polyclonal antiserum in in vitro cultured Plasmodium falciparum parasites, propagated in human red blood cells. PfNT3 protein, the translated product of PfNT3 gene was detected in intraerythrocytic ring, trophozoite, and schizont stages. PfNT3 was localized primarily to the PPM (Parasite Plasma Membrane). The endogenous PfNT3 putative nucleoside transporter with the predominant location to the parasite plasma membrane may serve not only as routes for targeting of purine analogs/cytotoxic agents into the intracellular parasite but may also serve as drug targets. Being genome encoded the vital transporter protein can be prevented from expression by silencing of the gene, validating it to be a novel drug target.